Clinical Characteristics and Predictors of 28-Day Mortality in 352 Critically Ill Patients with COVID-19: A Retrospective Study - Abdulrahman Alharthy; Waleed Aletreby; Fahad Faqihi; Abdullah Balhamar; Feisal Alaklobi; Khaled Alanezi; Parameaswari Jaganathan; Hani Tamim; Saleh A Alqahtani; Dimitrios Karakitsos; Ziad A Memish (Springer, 2020)
Background: Since the first COVID-19 patient in Saudi Arabia (March, 2020) more than 338,539 cases and approximately 4996 dead were reported. We present the main characteristics and outcomes of critically ill COVID-19 patients that were admitted in the largest Ministry of Health Intensive Care Unit (ICU) in Saudi Arabia. Methods: This retrospective study, analyzed routine epidemiologic, clinical, and laboratory data of COVID-19 critically ill patients in King Saud Medical City (KSMC), Riyadh, Saudi Arabia, between March 20, 2020 and May 31, 2020. Severe acute respiratory syndrome coronavirus-2 infection was confirmed by real-time reverse transcriptase polymerase chain reaction assays performed on nasopharyngeal swabs in all enrolled cases. Outcome measures such as 28-days mortality, duration of mechanical ventilation, and ICU length of stay were analyzed. Results: Three-hundred-and-fifty-two critically ill COVID-19 patients were included in the study. Patients had a mean age of 50.63 ± 13.3 years, 87.2% were males, and 49.4% were active smokers. Upon ICU admission, 56.8% of patients were mechanically ventilated with peripheral oxygen saturation/fraction of inspired oxygen (SpO2/FiO2) ratio of 158 ± 32. No co-infections with other endemic viruses were observed. Duration of mechanical ventilation was 16 (IQR: 8-28) days; ICU length of stay was 18 (IQR: 9-29) days, and 28-day mortality was 32.1%. Multivariate regression analysis showed that old age [Odds Ratio (OR): 1.15, 95% Confidence Intervals (CI): 1.03-1.21], active smoking [OR: 3, 95% CI: 2.51-3.66], pulmonary embolism [OR: 2.91, 95% CI: 2.65-3.36), decreased SpO2/FiO2 ratio [OR: 0.94, 95% CI: 0.91-0.97], and increased lactate [OR: 3.9, 95% CI: 2.4-4.9], and d-dimers [OR: 2.54, 95% CI: 1.57-3.12] were mortality predictors. Conclusion: Old age, active smoking, pulmonary embolism, decreased SpO2/FiO2 ratio, and increased lactate and d-dimers were predictors of 28-day mortality in critically ill COVID-19 patients.